Experiences of stigma and discrimination faced by family caregivers of people with schizophrenia in India. (April 2017) - Koschorke, Mirja; Padmavati, R.; Kumar, Shuba; Cohen, Alex; Weiss, Helen A.; Chatterjee, Sudipto; Pereira, Jesina; Naik, Smita; John, Sujit; Dabholkar, Hamid; Balaji, Madhumitha; Chavan, Animish; et al.
Abstract: Stigma associated with schizophrenia significantly affects family caregivers, yet few studies have examined the nature and determinants of family stigma and its relationship to their knowledge about the condition. This paper describes the experiences and determinants of stigma reported by the primary caregivers of people living with schizophrenia (PLS) in India. The study used mixed methods and was nested in a randomised controlled trial of community care for people with schizophrenia. Between November 2009 and October 2010, data on caregiver stigma and functional outcomes were collected from a sample of 282 PLS–caregiver dyads. In addition, 36 in-depth-interviews were conducted with caregivers. Quantitative findings indicate that 'high caregiver stigma' was reported by a significant minority of caregivers (21%) and that many felt uncomfortable to disclose their family member's condition (45%). Caregiver stigma was independently associated with higher levels of positive symptoms of schizophrenia, higher levels of disability, younger PLS age, household education at secondary school level and research site. Knowledge about schizophrenia was not associated with caregiver stigma. Qualitative data illustrate the various ways in which stigma affected the lives of family caregivers and reveal relevant links between caregiver-stigma related themes ('others finding out', 'negative reactions' and 'negative feelings and views about the self') and other themes in the data. Findings highlight the need for interventions that address both the needs of PLS and their family caregivers. Qualitative data also illustrate the complexities surrounding the relationship between knowledge and stigma and suggest that providing 'knowledge about schizophrenia' may influence the process of stigmatisation in both positive and negative ways. We posit that educational interventions need to consider context-specific factors when choosing anti-stigma-messages to be conveyed. Our findings suggest that messages such as 'recovery is possible' and 'no-one is to blame' may be more helpful than focusing on bio-medical knowledge alone. Highlights: Experiences of being blamed and worries about marital prospects were salient. Caregivers' and PLS' experiences of stigma were determined by similar factors. Knowledge was linked to stigma in qualitative but not in quantitative analyses. Context-specific messages rather than biomedical knowledge may help reduce stigma. Family caregivers need access to emotional and social support in their own right.